Theta band activity in response to emotional expressions and its relationship with gamma band activity as revealed by MEG and advanced beamformer source imaging - Luo, Qian; Cheng, Xi; Holroyd, Tom; Xu, Duo; Carver, Frederick W.; Blair, James (Frontiers in Human Neuroscience, 2014)
Neuronal oscillations in the theta and gamma bands have been shown to be important for cognition. Here we examined the temporal and spatial relationship between the two frequency bands in emotional processing using Magnetoencephalography and an advanced dynamic beamformer source imaging method called Synthetic Aperture Magnetometry. We found that areas including the amygdala, visual and frontal cortex showed significant event-related synchronization (ERS) in both bands, suggesting a functional association of neuronal oscillations in the same areas in the two bands. However, while the temporal profile in both bands was similar in the amygdala, the peak in gamma band power was much earlier within both visual and frontal areas. Our results do not support a traditional view that the localizations of lower and higher frequencies are spatially distinct. Instead, they suggest that in emotional processing, neuronal oscillations in the gamma and theta bands may reflect, at least in visual and frontal cortex either different but related functional processes or, perhaps more probably, different computational components of the same functional process.